The half-wetted bearing. Part 1: Extended Reynolds equation - Spikes,HA (Proceedings of the Institution of Mechanical Engineers, Part J: Journal of Engineering Tribology, 2003)
Recent research has shown that, when a liquid is partially wetting or non-wetting against a very smooth solid surface, the conventional no-slip boundary condition can break down. Under such circumstances, the Reynolds equation is no longer applicable. In the current paper, the Reynolds equation is extended to consider the sliding, hydrodynamic lubrication condition where the lubricant has a no-slip boundary condition against the moving solid surface but can slip at a critical shear stress against the stationary surface. It is shown that such a ‘half-wetted’ bearing is able to combine good load support resulting from fluid entrainment with very low friction due to very low or zero Couette friction.